A Study to Identify the Challenges in Talent Management in Indian It Sector: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Research aims to identify the challenges of talent management both for the organization as well as for employees with respect to IT sector. Sample of 60 employers from HCL, Wipro, TCS, Infosys and Tech Mahindra were used for the study, and data was analyzed using the factor analysis, Anova method and the descriptive analysis. Results showed that there are mainly six type of challenges in talent management in IT sector. These challenges were mainly risk factors, cost factors, Culture and working environment, Competition and external factors, Employees’ related factor, individual related factors. Challenges related to the risk factors were perceived to higher than other challenges and employees related challenges were perceived as low or not much challenges when compared to other challenges.